Two-loop leading-colour QCD helicity amplitudes for two-photon plus jet production at the LHC - Chawdhry, HA; Czakon, M; Mitov, A; Poncelet, R (Springer Nature, 2021)
We calculate the complete set of two-loop leading-colour QCD helicity amplitudes for γγj-production at hadron colliders. Our results are presented in a compact, fully-analytical form.